Genetic progress of upland rice between 1950 and 2001 - Souza, Moacil Alves de; Morais, Orlando Peixoto de; Herán, Roberto Evaristo Celi; Cargnin, Adeliano; Pimentel, Adérico Júnior Badaró (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this study was to quantify the genetic progress obtained by the genetic improvement of upland rice from 1950 to 2001. Four field experiments were conducted in the sites: Airport and Agronomy, in Viçosa, MG; in the farms Capivara and Palmital, in Santo Antônio de Goiás, GO, and Goianira, GO, respectively. The experiments were installed in a randomized block design, with three replications. Twenty-five cultivars planted in the period from 1950 to 2001 were assessed. Data of grain yield, plant height and days to flowering were collected and analyzed. In order to get the most accurate estimate of the genetic gain, the plants were separated in the groups of early and late cultivars. To estimate the genetic progress, a linear regression of the cultivar means per decade of use was performed. Genetic gains for grain yield were 0.3 and 2.09% per year in the early and late groups, respectively. Over the evaluated period, the mean plant height of the cultivars was reduced by 21 cm in the early group, and 38 cm in the late group. There was mean increase of ten days in the cycle of the early cultivar group and a decrease of 13 days of the late group.